ELECTRON-SPIN POLARIZATION IN THE DONOR TRIPLET-STATE OF BACTERIAL PHOTOSYNTHETIC REACTION CENTERS .2. ANISOTROPIC INVERSION OF ELECTRON-SPIN POLARIZATION IN A 3-SPIN MODEL REACTION CENTER - Hore, P; Hunter, D; Vanwijk, F; Schaafsma, T; Hoff, A (1988)
An explanation is proposed for the electron spin polarization pattern in the ΔmS = ± 1 EPR spectrum of the donor triplet state in pre-reduced Rhodopseudomonas viridis reaction centres at temperatures above 20 K. Calculations based on a simple model of the reaction centre indicate that rapid spin-lattice relaxation of the iron-semiquinone complex (QA-Fe2+) can perturb the polarization of the donor triplet provided the EPR frequency of QA-Fe2+ is close to that of P+ (the cation of the primary donor) and I- (the anion of the intermediary acceptor). In agreement with experimental observations, this mechanism only operates in the presence of a large exchange interaction between I- and QA-Fe2+. The observed anisotropy of this effect is attributed to the anisotropy of the resonance frequency of QA-Fe2+. © 1988.